О динамике линейного электромагнитного виброударного возбудителя - Божко, А.Е.; Белых, В.И. (Доповіді НАН України, 2010)
Наводиться метод вивчення перемiщень якоря в лiнiйному електромагнiтному вiброударному збуджувачi при вхiдних впливах у виглядi прямокутних iмпульсiв. Цi впливи подано як сингулариснi розкладення стрибкоподiбної функцiї. The method to determine a displacement of the rotor in a linear electromagnetical vibrostroke exciter with the influence of input rectangular impulses is given. This influence is presented in the form of the singularisnal expansion of a jump-like function.